Country-specific investment motivations in Central Europe: Evidence from British firms - Shaukat Ali; Hafiz Mirza (Journal for East European Management Studies, 1998)
The countries of Eastern and Central Europe have been progressing on the road to a market economy for a number of years now. UK companies, like other western firms, aware of the region's inhabitants pent-up desire for numerous consumer and industrial products and services have invested significantly. This paper presents empirical data of UK firms' country-specific motivations for investing in three Visegrád countries: Hungary Poland and the Czech Republic. Just over 40 per cent of the firms had investments in one country only. Various country-specific reasons were cited by the respondents, the significant of which were those relating to market-orientated factors and strategic factors. There was no statistical difference between the reasons chosen for each, except that of profit, where Hungary significantly differed from Poland and Czechia. – – Die Länder Ost- und Mitteleuropas befinden sich nun schon einige Jahre auf dem Weg in die soziale Marktwirtschaft. Britische Unternehmen haben, wie andere westliche Firmen auch, hier erheblich investiert, da sie den unerschöpflichen Nachholbedarf der Einwohner dieser Länder bezüglich zahlreicher Konsum- und Investitionsgüter sowie Dienstleistungen erkannt haben. Der vorliegende Artikel basiert auf empirischen Daten zu länderspezifischer Investitionsgründen britischer Unternehmen in Polen, Tschechien und Ungarn. Die Befragten nannten vorwiegend marktorientierte und strategische Motive. Zwischen einzelnen Ländern konnten keine signifikanten Unterschiede festgestellt werden. Einzige Ausnahme hiervon bildet das Motiv 'Gewinnstreben' bei Investitionen in Ungarn.
Keywords: 650